“EVALUATION OF GALPHIMIA GLAUCA STEM METHANOL EXTRACT FRACTIONS FOR ANALGESIC AND ANTI-INFLAMMATORY ACTIVITIES” - GARIGE BABA SHANKAR RAO; SRISAILAM K; V UMA MAHESHWARA RAO; VASUDHA B (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This current investigation assesses in vivo central and peripheral analgesic effects and anti-inflammatory properties of fractions obtained from Galphimia glauca (GG) stem methanol extract. Methods: The laboratory models such as Swiss albino mice and Wistar albino rats were employed in the studies. The GG stem methanol extract was subjected to fractionation with solvents such as hexane, chloroform, ethyl acetate, and methanol. Orally, the dose range of 100, 200, and 400 mg/kg was given for 1 day for evaluating analgesic (hotplate test, tail clip test, writhing test, and formalin test) and weekdays for assessing anti-inflammatory activity (carrageenan and cotton pellet test methods), respectively. The experimental studies were further conducted for determining the involvement of central and peripheral receptor actions in the analgesic activity of the extract by prechallenging it with naloxone and acetic acid, respectively. The in vivo anti-inflammatory studies were conducted using carrageenan-induced rat paw edema model and cotton pellet granuloma test. Results: The LD50 of the extract was found to be >2000 mg/kg b.w. The methanol fraction of 400 mg/kg dose exhibited significant (p≤0.001) and dose-dependent analgesic and anti-inflammatory activity. It also exhibited central and peripheral analgesic actions when treated with naloxone and acetic acid, respectively. Conclusion: The results revealed that the stem methanol fraction has more potential in terms of analgesic and anti-inflammatory properties.